Análise do consumo de aço em estruturas otimizadas submetidas a diferentes concepções estruturais - Faria, Luis Fernando de (2021)
Project optimization is a tool that points out ways to achieve efficiency in the design of steel structures. For this reason, she is essential when speaking in the 21st century about resource rationalization. In this context, this research aimed to analyze the steel consumption of a hypothetical building characterized in nine design arrangements, where they were distinguished by their external measure and also by their type of modeling. Therefore, the structure was dimensioned and optimized in the structural calculation software CYPE 3D. Steel consumption was illustrated using indices obtained in the analysis and results process, where the program generated the steel quantities in the form of a report. With these results, it was possible to establish the ideal steel consumption for each structural design and mathematically describe the correlation of these data, thus obtaining consumption indicators for similar structures, meeting all the criteria of the Brazilian steel structure standard.